Social media and academic success: Impacts of using telegram on foreign language motivation, foreign language anxiety, and attitude toward learning among EFL learners - Zhao, Zhongzheng; Wang, Xiaochuan; Ismail, Sayed M.; Hasan, Md. Kamrul; Hashemifardnia, Arash (Frontiers in Psychology, 2022)
Concerning the ubiquity of social media, this research tried to examine the impacts of using Telegram on Iranian EFL learners’ foreign language motivation, foreign language anxiety, and attitude toward learning. To achieve these purposes, 60 Iranian EFL learners at the intermediate level were selected and randomly divided into two groups of experimental and control. After that, both groups were pretested on motivation and anxiety variables. After pretesting, the participants in the experimental class received the treatment via using the Telegram application and the control students were trained traditionally without using any social media. After an 18-session instruction, a post-test of motivation and a post-test of anxiety were given to both groups and also an attitude questionnaire was distributed among the experimental group to inspect their attitudes toward the Telegram application in language learning. The results of using two One-way ANCOVA tests showed significant differences between the post-tests of the control and experimental groups in favor of the experimental group. The findings demonstrated that using the Telegram application increased the motivation of the experimental group and decreased their level of foreign language anxiety. Also, the results of One sample t-test showed that the experimental group participants held positive attitudes toward using the Telegram application in English language learning. The implications of this research can encourage both teachers and learners to use social media-based instruments in English teaching and learning.